(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
We analyze, from a perspective of synthesis history, some speeches of political actors in times of mandate in Venezuela of the Revolutionary Government Board and Romulo Gallegos, about the direction that should lead the country, using oil income for economic growth in line with emerging parameters of the post-war modernization, as well as the “fifty fifty” agreement between the Venezuelan State and oil companies, linking both issues with global oil dynamics